The Impact of Geopolitics on the State Behavior in Tajikistan - Hamid Hakim (دولت‌پژوهی, 2021)
Owing to their lasting and permanent effects, geopolitical factors play a significant role in the politics and behavior of state. Given Tajikistan’s geopolitics, it is important to consider geopolitical factors and their effects in order to understand and predict policies and behavior of the state in Tajikistan. This is also of special importance due the proximity of Tajikistan to the Islamic Republic of Iran as well as myriad commonalities between the two. Adopting a descriptive–analytical method and relying on library research, the present study aims to analyze the politics and behavior of the state in Tajikistan by investigating the effects of Tajikistan’s geopolitics on the state. The hypothesis is that the geopolitical characteristics of Tajikistan are factors causing tension for the country and creating, directly or indirectly, threats, instability, and insecurity which all affect the politics and behavior of the state in Tajikistan. This has led to the state’s authoritarianism and centralism in the domestic arena and its dominated, submissive character in the foreign arena.